Driving heat ebook Nikki heat book 7. - Castle, Richard (Nikki Heat, 2015)
Richard Castle, New York Times mega-bestselling mystery writer and star of ABC's hit primetime show Castle is back. In the seventh novel of his popular Nikki Heat series, the NYPD's top homicide detective has been promoted to captain just in time to face a thrilling case with a very personal twist. Captain Heat's fiancé, Pulitzer Prize-winning reporter Jameson Rook, is deep in an investigation. Professionally for Heat, Rook's meddling in the case compromises her new job. Privately, it becomes an early test of their engagement when Rook becomes a distraction at best, and an obstacle at worst, as their parallel lives not only cross, but collide.